(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
The study investigated the role of social media in development communication: opportunitiesand challenges. The study revealed that Nigeria’s evolving communication landscape, is driven by a blend of traditional media and the rapid rise of social media, has significantly influenced the country’s socio-economic development. Social media platforms such as Facebook, Twitter, and Instagram have redefined communication by facilitating public engagement, fostering transparency, and amplifying voices of marginalized groups. This digital shift has allowed for increased civic participation and empowered communities to mobilize on critical issues. The #EndSARS movement, for instance, showcased how social media can bring national and global attention to social justice causes, reflecting the transformative potential of digital platforms in fostering democratic values and driving change. While social media provides new opportunities for development communication, its effectiveness hinges on factors like digital literacy and equitable access. This study thus investigates the dual role of social media in advancing development communication in Nigeria, focusing on the challenges and opportunities it presents in the nation’s socio-political context.